Self-care, A1C and stigmatization as predictors of a negative perception of insulin among adults with type 2 diabetes: a hospital-based study in Turkey - Hamdiye Arda Sürücü; Hatice Okur Arslan; Sıdıka Çetik (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The purpose of this study was to investigate diabetes self-care behaviors, stigmatization and A1C as predictors of a negative perception of insulin treatment in insulin-treated type 2 diabetic patients. Design/methodology/approach - A descriptive cross-sectional and relational design was used. The study was carried out in the Diabetes Training Centre and Endocrine and Metabolism Clinic of a university hospital in the southeast of Turkey between May and October 2017. The research sample consisted of 100 type 2 diabetic patients determined by using a convenience sampling method. An introductory information form for type 2 diabetic patients, the Insulin Treatment Appraisal Scale (ITAS), Diabetes Self-Care Activities Survey (DSCAS) and Barriers to Insulin Treatment Scale (BIT) were used to collect the research data. The data were analyzed using descriptive statistics, correlations and step wise multi-linear regression. Findings - The number of daily insulin injections, training received about insulin and stigmatization was significant predictors of a negative perception of insulin treatment. Originality/value - Strategies to decrease diabetic individuals' fear of stigmatization should be utilized to minimize their negative insulin treatment perception (giving diabetic individuals training about diabetes, planning public training to inform society and using mass media tools). Diabetes educators should know that diabetic individuals' perception of the severity of the illness could influence the daily number of injections applied and decrease the negative perception regarding insulin.